Mechanisms and therapeutic implications of selective autophagy in nonalcoholic fatty liver disease: medicine - Jin, Suwei; Li, Yujia; Xia, Tianji; Liu, Yongguang; Zhang, Shanshan; Hu, Hongbo; Chang, Qi; Yan, Mingzhu (Journal of advanced research, 2025)
Background - Nonalcoholic fatty liver disease (NAFLD) has become the most common chronic liver disease worldwide, whereas there is no approved drug therapy due to its complexity. Studies are emerging to discuss the role of selective autophagy in the pathogenesis of NAFLD, because the specificity among the features of selective autophagy makes it a crucial process in mitigating hepatocyte damage caused by aberrant accumulation of dysfunctional organelles, for which no other pathway can compensate. - Aim of review - This review aims to summarize the types, functions, and dynamics of selective autophagy that are of particular importance in the initiation and progression of NAFLD. And on this basis, the review outlines the therapeutic strategies against NAFLD, in particular the medications and potential natural products that can modulate selective autophagy in the pathogenesis of this disease. - Key scientific concepts of review - The critical roles of lipophagy and mitophagy in the pathogenesis of NAFLD are well established, while reticulophagy and pexophagy are still being identified in this disease due to the insufficient understanding of their molecular details. As gradual blockage of autophagic flux reveals the complexity of NAFLD, studies unraveling the underlying mechanisms have made it possible to successfully treat NAFLD with multiple pharmacological compounds that target associated pathways. Overall, it is convinced that the continued research into selective autophagy occurring in NAFLD will further enhance the understanding of the pathogenesis and uncover novel therapeutic targets.